How trauma patients die in low resource settings: Identifying early targets for trauma quality improvement. Issue 2 (27th February 2023) - Christie, S. Ariane; Zheng, Dennis; Dissak-Delon, Fanny; Kinge, Thompson; Njock, Richard; Nkusu, Daniel; Tsiagadigui, Jean-Gustave; Mbianyor, Mbiarikai; Dicker, Rochelle; Chichom-Mefire, Alain; Juillard, Catherine
Abstract : Death analysis from a prospective, multicenter sub-Saharan African cohort found trauma deaths are associated with critical deficits in completion of primary survey interventions including correction of respiratory distress, hemorrhage, and traumatic brain injury. Abstract : BACKGROUND: Injury deaths in sub-Saharan Africa are among the world's highest, but hospital data rarely have sufficient granularity to direct quality improvement. We analyzed clinical care patterns among trauma patients who died in a prospective, multicenter sub-Saharan cohort to pinpoint trauma quality improvement intervention targets. METHODS: In-hospital trauma deaths in four Cameroonian hospitals between 2017 and 2019 were included. Trauma registry data on patient demographics, injury characteristics, and clinical care were analyzed to identify opportunities for systems improvements. RESULTS: Among 9, 423 trauma patients, there were 236 deaths. Overall, 83% of patients who died in the emergency department were living on arrival (LOA). Among 183 LOA patients, 30% presented with normal vital signs, but 11% had no vital signs taken, often because of lack of equipment (43%). Of LOA patients presenting with a Glasgow Coma Scale score of <9 (56%), few received neurosurgery consults (15%), C-collar placement (9%), or intubation (1%). The most common reason for lack of c-collar placement was failure to recognize that it was indicated (66%). Tracheal deviation, unequal breath sounds, or paradoxical chest movement were present in 63% of LOA patients, but only two patients had chest tubes placed. Hypotension or active bleeding was present in 80% of LOA patients; while crystalloid bolus was given to 96% of these patients, few received transfusion (8%), tourniquet placement for extremity injury (6%), or an operation (4%). CONCLUSION: Primary survey interventions are underperformed in trauma nonsurvivors in Cameroon. Protocolizing early treatment for head injury, hemorrhagic shock, and chest wall trauma could reduce trauma mortality. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; Level III. Abstract :